The role of members of the pertussis toxin-sensitive family of G proteins in coupling receptors to the activation of the G protein-gated inwardly rectifying potassium channel - Leaney, Joanne Louise (The National Academy of Sciences, 2000)
Inwardly rectifying potassium (K(+)) channels gated by G proteins (Kir3.x family) are widely distributed in neuronal, atrial, and endocrine tissues and play key roles in generating late inhibitory postsynaptic potentials, slowing the heart rate and modulating hormone release. They are directly activated by G(βγ) subunits released from G protein heterotrimers of the G(i/o) family upon appropriate receptor stimulation. Here we examine the role of isoforms of pertussis toxin (PTx)-sensitive G protein α subunits (G(iα1–3) and G(oαA)) in mediating coupling between various receptor systems (A(1), α(2A), D(2S), M(4), GABA(B)1a+2, and GABA(B)1b+2) and the cloned counterpart of the neuronal channel (Kir3.1+3.2A). The expression of mutant PTx-resistant G(i/oα) subunits in PTx-treated HEK293 cells stably expressing Kir3.1+3.2A allows us to selectively investigate that coupling. We find that, for those receptors (A(1), α(2A)) known to interact with all isoforms, G(iα1–3) and G(oαA) can all support a significant degree of coupling to Kir3.1+3.2A. The M(4) receptor appears to preferentially couple to G(iα2) while another group of receptors (D(2S), GABA(B)1a+2, GABA(B)1b+2) activates the channel predominantly through G(βγ) liberated from G(oA) heterotrimers. Interestingly, we have also found a distinct difference in G protein coupling between the two splice variants of GABA(B)1. Our data reveal selective pathways of receptor activation through different G(i/oα) isoforms for stimulation of the G protein-gated inwardly rectifying K(+) channel.